"It is usually about the triumph of the coloniser": Exploring young people's conceptualisations of Australian history and the implications for Australian identity. (5th September 2018) - Farrugia, Jack P.; Dzidic, Peta L.; Roberts, Lynne D.
Abstract: Australians of European descent reconstruct Australian history to silence the mistreatment of Indigenous Australians and to favour the coloniser perspective. Literature suggests that although this reconstructed history is typically accepted uncritically, in recent times, young people may have become more critical of this historical account. Exploring young people's conceptualisations of Australian history may provide insight into emerging perspectives of Australian history, and ultimately young people's understanding of Australian identity. A qualitative research design with a social constructionist approach was adopted. Twelve young people aged 18 to 25 who self‐identified as having an interest in Australian history were recruited and participated in a semistructured interview. Interview transcripts were analysed thematically. Three major themes emerged: "learning and 'relearning' Australian history, " "making sense of what is happening, " and "who is an Australian?" Viewed through a Freirean lens, some young Australians of European descent appear to be undergoing a conceptual shift from holding perspectives associated with the oppressor to adopting a more critical stance of Australian history. Despite this, understandings of oppression were at times paradoxical. Further research is required to understand the phenomena of this proposed shift and to facilitate and encourage this process of siding with the oppressed.